Polylactide‐block‐Polypeptide‐block‐Polylactide Copolymer Nanoparticles with Tunable Cleavage and Controlled Drug Release. (14th March 2014) - Dorresteijn, Robert; Billecke, Nils; Schwendy, Mischa; Pütz, Sabine; Bonn, Mischa; Parekh, Sapun H.; Klapper, Markus; Müllen, Klaus
Abstract : A versatile nanoparticle system is presented in which drug release is triggered by enzymatic polymer cleavage, resulting in a physicochemical change of the carrier. The polylactide‐ block ‐peptide‐ block ‐polylactide triblock copolymer is generated by initiation of the ring‐opening polymerization of L‐lactide with a complex bifunctional peptide having an enzymatic recognition and cleavage site (Pro‐Leu‐Gly‐Leu‐Ala‐Gly). This triblock copolymer is specifically bisected by matrix metalloproteinase‐2 (MMP‐2), an enzyme overexpressed in tumor tissues. Triblock copolymer nanoparticles formed by nonaqueous emulsion polymerization are readily transferred into aqueous media without aggregation, even in the presence of blood serum. Cleavage of the triblock copolymer leads to a significant decrease of the glass transition temperature (Tg ) from 39 °C to 31 °C, likely mediating cargo release under physiological conditions. Selective drug targeting is demonstrated by hampered mitosis and increased cell death resulting from drug release via MMP‐2 specific cleavage of triblock copolymer carrier. On the contrary, nanocarriers having a scrambled (non‐recognizable) peptide sequence do not cause enhanced cytotoxicity, demonstrating the enzyme‐specific cleavage and subsequent drug release. The unique physicochemical properties, cleavage‐dependent cargo release, and tunability of carrier bioactivity by simple peptide exchange highlight the potential of this polymer‐nanoparticle concept as platform for custom‐designed carrier systems. Abstract : Triblock copolymer nanoparticle with tunable drug release . Nanocarriers based on PLLA‐ b ‐peptide‐ b ‐PLLA copolymers are proved to have exceptional material properties for controlled drug release in response to MMP‐2‐dependent peptide cleavage. Comparison specimens demonstrate the tunable bioactivity of these nanocarriers based on polymer constitution. As MMP‐2 is selectively overexpressed in tumor tissues, this is a promising system for solid tumor cancer therapy.